The Association Between Precuneus Function and Residual Dizziness in Patients With Benign Paroxysmal Positional Vertigo - Fu, Wei; Bai, Ya; He, Feng; Wei, Dong; Wang, Yuanyuan; Shi, Ying; An, Xinyue; Han, Junliang; Wang, Xiaoming (Frontiers in Neurology, 2022)
Background: Residual dizziness(RD) is the complications after benign paroxysmal positional vertigo(BPPV) treatment. The precuneus, located in the posteromedial parietal lobe, is considered to play a central role in symptoms of dizziness. However, the effects of precuneus function on RD in BPPV are yet to be investigated. Objectives: The purpose of this brief research report was to apply the amplitude of low-frequency fluctuation (ALFF) method to investigate the spontaneous brain activity alterations in patients with RD. Methods: All patients underwent visual vertigo analogue scale(VVAS) evaluations and functional magnetic resonance imaging (fMRI). The ALFF method was used to assess the spontaneous brain activity. Screening of brain regions with significant changes in ALFF values was based on analysis of the whole brain. We further analyze the relationship between ALFF values of the altered regions and VVAS scores in patients with RD. Results: Fifteen BPPV patients with RD and fifteen without RD were recruited in this study. In contrast to without RD, RD patients exhibited increased scores in VVAS tests (p<0.001) and RD patients also showed significant ALFF decrease in the bilateral precuneus(left: 251 voxels; x=-10, y=-69, z=51; peak t-value=-3.25; right: 170 voxels; x=4, y=-59, z=42; peak t-value=-3.43). Correlation analysis revealed that the mean ALFF z-values in the left precuneus displayed significant negative correlations with the VVAS scores(r=-0.44, p=0.01). Conclusions: This study shows that RD in BPPV are associated with left precuneus function as revealed by fMRI. It might provide useful information for explaining neural mechanisms in patients with RD.